1991
DOI: 10.1152/ajpheart.1991.261.6.h1716
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxic pulmonary hypertension in rats and increased elastolytic activity

Abstract: Previously in rats injected with the toxin monocrotaline and administered SC-39026, a serine elastase inhibitor, pulmonary hypertension was decreased in association with reduced muscularization of peripheral pulmonary arteries. To determine whether inhibition of elastolytic activity might prevent this vascular change in other conditions producing pulmonary hypertension, we administered SC-39026 to rats during a 10-day exposure to chronic hypobaric hypoxia. We also measured elastolytic activity in the central p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 0 publications
5
100
0
Order By: Relevance
“…We identified the elastase involved as neutrophil elastase (NE) produced by PA SMC, suggesting that it is the endogenous vascular elastase previously related to PAH in other experimental models. 12,16,18,19 Moreover, we showed that NE is produced in significantly greater amounts by cultured murine S100A4 versus C57 PA SMC, and by human PA SMC from IPAH versus control lungs, and we localized NE to neointimal and plexiform lesions in human lung specimens.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…We identified the elastase involved as neutrophil elastase (NE) produced by PA SMC, suggesting that it is the endogenous vascular elastase previously related to PAH in other experimental models. 12,16,18,19 Moreover, we showed that NE is produced in significantly greater amounts by cultured murine S100A4 versus C57 PA SMC, and by human PA SMC from IPAH versus control lungs, and we localized NE to neointimal and plexiform lesions in human lung specimens.…”
mentioning
confidence: 78%
“…opathy after transplantation, 28,51 vein graft atherosclerosis 52 and fibrosis following viral myocarditis, 53,54 or pulmonary hypertension induced by hypoxia 12,14 or monocrotaline. 13,15 In five of these models, 28,50,52,54 elafin was used as the elastase inhibitor, given as an infusion, 28 by gene therapy 50,52 or in an overexpressing transgenic mouse.…”
Section: Grade Imentioning
confidence: 99%
See 1 more Smart Citation
“…After the hypoxic exposure period, the rats were anaesthetised with pentobarbital sodium (45 mg?kg -1 ) given intraperitoneally. A pulmonary artery catheter (Silastic tubing, 0.31 mm inside diameter (ID) and 0.64 mm outside diameter (OD)) was inserted via the right external jugular vein into the pulmonary artery by a closed-chest technique, as described previously [8,10]. The catheter was then tunnelled subcutaneously and exteriorised in the middle region of the scapular of the rat.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the relationship between the hypertensive pulmonary vascular changes and response to inhaled NO, NO inhalation was carried out in a rat model of chronic PH induced by chronic hypoxic exposure of varying durations. Quantitative morphometrical analysis was applied to determine the severity of hypertensive pulmonary vasculature [8][9][10]. Low-dose NO inhalation ¡2 parts per million (ppm) was chosen because a lower dose is favourable to minimise any possible toxicity.…”
mentioning
confidence: 99%